ANALISA PROSES ADMINISTRASI PERJALANAN DINAS KARYAWAN PT. XYZ MENGGUNAKAN METODE WHY-WHY ANALYSIS - Imas Widowati; Dedi Purwanto (Jurnal Teknologika, 2019)
In the implementation process of the administration of official travel that undertaken by executive staff of Payroll and outsourcing management’s work unit, Human resource management department, often facing the problems in the terms of accountability of official travel documents that can hinder the performance of the staff. Root Cause Analysis with why-why analysis methods can be used to analyze and find the root of a problem and then will generate the appropriate action to handle the problems that often arise in the implementation process of the administration of official travel in the future.